Some suggestions for Urban planning approach to Green Infrastructure, implications for Vinh city, Nghe An province, Viet Nam - Nguyen-Thi Kieu-Vinh; Doan-Thi Thuy-Huong (E3S Web of Conferences, 2021)
Research on green infrastructure has become a mainstream of managers, planners and architects around the world given its utmost impacts on human life and nature. Green infrastructure protection and development in urban management, planning, design and construction represents an important task to ensure sustainable development. This article presents some suggestions for urban planning approach to green infrastructure, contributing to the protection and development of this system.